The Value Relevance of Accounting Information in Financial Industry : 15-Year Perspective - Phakdee, Anuwat; Srijunpetch, Sillapaporn (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2020)
The purpose of this study is to examine the relevance of book value and earnings per share on stock price of the financial industry in the Stock Exchange of Thailand. In addition, the incremental value relevance of book value and earnings per share is tested. The secondary data is collected SETSMART online database over the 15-year period from 2004 – 2018 of 762 examples. The relevance and comparison of the increment of book value and earnings per share is analyzed by regression analysis techniques based on valuation model of Ohlson (1995). The results find that book value and earnings per share are statistically significantly associated with stock price. From the incremental relevance analysis, the results show that book value and earnings per share of the financial industry have been associated with stock prices over fifteen years, indicating the usefulness of accounting information for decisions. In addition, the research findings show that earnings have more incremental value relevance than book value from 2009 to 2018 continuously.